1993
DOI: 10.1139/b93-178
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of spatial heterogeneity of vesicular–arbuscular mycorrhizal fungi in two maple-forest soils

Abstract: The variations in the numbers of propagules and in the colonization rates of vesicular–arbuscular mycorrhizal fungi in soils of two sugar maple forests, one near Waterloo in southern Ontario, the other near Lacolle in southern Quebec, were investigated. Both forests comprised similar plant communities, and in each case the most numerous mycorrhizal spores were identified as those of Glomus macrocarpum, Glomus geosporum, and Acaulospora foveata. In both forests, root colonization and length of hyphae in soil pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 0 publications
1
50
0
4
Order By: Relevance
“…Variations in moisture (Anderson et al, 1983), organic matter content (Klironomos et al, 1993), pH (Robson & Abbott, 1989), and temperature (Koske, 1987) may affect abundance of AMF spores.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in moisture (Anderson et al, 1983), organic matter content (Klironomos et al, 1993), pH (Robson & Abbott, 1989), and temperature (Koske, 1987) may affect abundance of AMF spores.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in forests inoculum potential could be influenced by a bewildering array of soil and host plant characteristics. Heterogeneity in inoculum potential in soils has been observed at both small (from adjacent cores), and larger scales (among transects, Brundrett and Abbott 1995), over different soil types (Porter 1979, Klironomos et al 1993, Klironomos 1995, gradients in disturbance (Koide and Mooney 1987, Alexander et al 1992, Fischer et al 1994, Boerner et al 1996, Brundrett et al 1996b, and vegetation types (Koide and Mooney 1987, Asbjornsen and Montagnini 1994, Brundrett et al 1996a. To test whether heterogeneity in inoculum potential varies predictably with host tree or soil factors within a temperate broadleaved forest we used a bioassay.…”
Section: Introductionmentioning
confidence: 99%
“…This variation could attribute to the differences in soil moisture and organic matter contents of both regions and could influence the growth and chemical constituents of S. persica collected from these regions. Fitter et al (2000) and Jeffries et al (2003) type has been reported to affect the degree of specialization exhibited by AMF (Klironomos et al,1993) as well as their growth and colonization (Abler, 2004). Many reports have shown that AMF play an important role in helping plants withstand water deficiency (Augé, 2001;Augé, 2004;Aroca et al, 2008).…”
Section: Discussionmentioning
confidence: 99%